Xanthine Oxidase and Paraoxonase – 1 as a new markers in the diagnosis and prognosis of organophosphorus pesticide poisoning - Kale, Bhagwat (International Journal of Biological Research, 2013)
Background: Acetylcholinesterase is already well known marker for organophosphorus poisoning in human beings. But, our interest was to known for another new markers. There is high limited study on xanthine oxidase and paraoxonase 1 in human beings having organophosphorus poisoning. Thus, aim of our this research was to estimate and correlate activities of xanthine oxidase and paraoxonase 1 in different stages of organophosphorus poisoning in a way to find out potential of these enzymes as marker of organophosphorus poisoning in human beings. Method: Xanthine oxidase (XO) activity was determined by Roussos method while paraoxonase (PON1) activity was determined by spectrophotometric method. Result: As compared to healthy controls, the activities of paraoxonase 1 were continuously and significantly decreased (p < 0.01) from group I to group V, while, the activities of xanthine oxidase were continuously and significantly increased (p < 0.01) from group I to group V in organophosphorus poisoned patients. Conclusion: We found a proportional increase in xanthine oxidase (XO) and a proportional decrease in paraoxonase 1 activity with severity of organophosphorus poisoning. Increase in xanthine oxidase activity is less significant compared to decrease in activity of paraoxonase 1. However, xanthine oxidase activity is a marker of oxidative stress developed in organophosphorus poisoning. Thus, paraoxonase 1 (PON1) can be used as a potent biochemical marker in the diagnosis and prognosis of organophosphorus poisoning along with xanthine oxidase (XO).